The feasibility of electromagnetic sensing aided post pyloric feeding tube placement (CORTRAK) in patients with thrombocytopenia with or without anticoagulation on the intensive care unit. Issue 5 (29th October 2021) - Stecher, Stephanie Susanne; Barnikel, Michaela; Drolle, Heidrun; Pawlikowski, Alexandra; Tischer, Johanna; Weiglein, Tobias; Alig, Annabel; Anton, Sofia; Stemmler, Hans Joachim; Fraccaroli, Alessia
Abstract: Background: The successful initiation of enteral nutrition is frequently hampered by various complications occurring in patients treated in the intensive care unit (ICU). Successful placement of a nasojejunal tube by CORTRAK enteral access system (CEAS) has been reported to be a simple bedside tool for placing the postpyloric (PP) feeding tube. Methods: We evaluated the efficacy and side effects using CEAS to establish EN in patients with critical illness, thrombocytopenia, and/or anticoagulation. Results: Fifty‐six mechanically ventilated patients were analyzed. Twenty‐four of them underwent prior hematopoietic stem cell transplantation (SCT). Sixteen patients received extracorporeal membrane oxygenation treatment because of acute respiratory distress syndrome. The median platelet count at PP placement was 26 g/L (range, 4–106 g/L); 16 patients received therapeutic anticoagulation (activated partial thromboplastin time, 50–70 s). CEAS‐assisted placement of a PP nasojejunal tube was performed successfully in all patients. The most frequent adverse event was epistaxis in 27 patients (48.2%), which was mostly mild (Common Terminology Criteria for Adverse Events grade 1, n = 21 [77.8%], and grade 2, n = 6). A significant association between a low platelet count and bleeding complications was observed ( P < 0.001). Conclusion: Performed by an experienced operator, CEAS is a simple, rapidly available, and effective bedside tool for safely placing PP feeding tubes for EN in patients with thrombocytopenia, even when showing an otherwise‐caused coagulopathy in the ICU. Higher‐grade bleeding complications were not observed despite their obvious correlation to thrombocytopenia. A prospective study is in preparation.